STRATEGI KELANGSUNGAN USAHA KEDAI KOPI DI SURAKARTA PADA MASA PANDEMI COVID-19 - Khoirul Fajri, Muhamad; Nugroho, Wahyu Budi; Krisna Aditya, I Gusti Ngurah Agung (JURNAL ILMIAH SOSIOLOGI: SOROT; Vol 1 No 01 (2021): JISSOROT, 2021)
A coffee shop is a place that provides various types of processed coffee. The sustainability of the coffee shop experienced a few obstacles when facing the current state of the covid-19 pandemic. This study uses a qualitative approach with a descriptive-explanative type of research. The theory used in this research is James S. Coleman's rational choice theory. This study examines the strategy for the sustainability of coffee shops in Surakarta City during the COVID-19 pandemic. Based on the results of this study, an appropriate strategy is needed to maintain the sustainability of coffee shops during the current pandemic. Some of the strategies used by coffee shops in Surakarta City and considered cost-effective, such as discount promos and bundling packages, implementing employee work shifts, adding new menus and coffee education through social media to consumers. This study also explains the impact of the COVID-19 pandemic on the sustainability of coffee shops. Keywords: Coffee Shop, Strategy, Covid-19, Rational Choice